Strategy Formulation Roadmap Human Capital: Action Research Based Soft System Methodology, Case in PT Angkasa Pura I - Sakapurnama, Eko; Umanto, Umanto; Muslim, Muh Azis; Asriyadi, Dony (School of Business and Management Institut Teknologi Bandung, 2020)
Abstract. In the era of war for talent, attracting and retaining the talented people become necessary to gain organization’s competitive advantage. Facing the airport industry in the regional area that become more competitive, PT Angkasa Pura I, try to formulate its key competence called World Class Airport Officer (WCAO). This study aims to formulate strategically within human resources for all PT Angkasa Pura I’s staff. The method of the research is using Soft Systems Methodology (SSM). SSM is implemented with the consideration that the implementation of the Human Capital’s Strategy Formulation is seen as a human activity system, which involves many stakeholders among top executives, Branch Managers, Human Capital Division Head, Training and Development Department Head, Organizational Development Department Head and all employees. The result indicates that management conducted learning process which are systematically desirable and culturally feasible in formulating Human Capital Road Map to achieve WCAO. Furthermore, the competencies of WCAO consists of innovative, professional, collaborative minded, service oriented, integrity and also be proactive.Keywords: Business strategy, soft system methodology, strategic human resource management, strategy formulation, airport industry